Conversion of Isopropanol to Diisopropyl Ether over Cobalt Phosphate Modified Natural Zeolite Catalyst - Hasanudin, Hasanudin; Asri, Wan Ryan; Rahmawati, Rahmawati; Riyanti, Fahma; Maryana, Roni; Al Muttaqii, Muhammad; Rinaldi, Nino; Hadiah, Fitri; Novia, Novia (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
This study aims to produce diisopropyl ether (DIPE) via isopropanol dehydration using cobalt-phosphate-supported natural zeolite catalysts. The catalytic activities of the zeolite/CoO and zeolite/Co(H2PO4)2 were compared. The as-prepared catalysts were assessed using X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared (FTIR) spectroscopy, and N2 adsorption-desorption. Surface acidity was determined using the gravimetric method with pyridine as the probe. The results of this study showed that natural zeolite was favorably impregnated by CoO and Co(H2PO4)2 species. The impregnation process affected the textural and acidic features of the catalysts. The zeolite/Co(H2PO4)2 catalyst with a loading of 8 mEq.g-1 exhibited the highest surface acidity of 1.827 mmol.g-1. This catalyst also promoted the highest catalytic activity towards isopropanol dehydration, with an isopropanol conversion of 66.19%, DIPE selectivity, and yield of 46.72% and 34.99%, respectively. The cobalt phosphate species promoted higher catalytic activity for isopropanol dehydration than the CoO species. This study demonstrated the potential of cobalt phosphate-supported natural zeolite catalysts for DIPE production with adequate performance. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).